SKRINING DAN ANALISIS FITOKIMIA TUMBUHAN OBAT TRADISIONAL MASYARAKAT KABUPATEN BIMA - Azmin, Nikman; Rahmawati, Anita (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2019)
Phytochemical Screening and Analysis of Traditional Herbal MedicinesÃ‚Â of Bima DistrictBima people use medicinal plants for traditional medicine which is local wisdom that must be preserved. Thus, the phytochemical content of these plants needs to be studied. This study aims to determine the secondary metabolite content of traditional medicinal plants in order to enrich biotechnology and pharmacological data. Thus, the data can be used as a reference in healing diseases and managing various medicinal plants based on community welfare and environmental sustainability for the people of Bima regency. The method used is a detailed interview and a field survey followed by phytochemical screening to determine the content of compounds in plants. From the results of this study, as many as 17 types of medicinal plants have been used as traditional medicine. The plant parts used are leaves, stems, flowers, roots, rhizomes, fruit, gum or lenders with 33% weed habitus followed by herbs (29%), trees (29%), and shrubs (9%). The compounds identified in these medicinal plants are flavonoids, alkaloids, steroids, terpenoids, saponins, and tannins.Keywords: Bima regency; local wisdom; medicinal plants; phytochemicals; secondary metabolitesABSTRAKMasyarakat Bima memanfaatkan tumbuhan obat untuk pengobatan tradisional yang merupakan kearifan lokal yang harus dipertahankan, sehingga kandungan fitokimia dari tumbuhan-tumbuhan ini perlu diteliti. Penelitian ini bertujuan untuk mengetahui kandungan metabolit sekunder tumbuhan obat tradisional guna memperkaya data bioteknologi dan farmakologi. Dengan demikian, data tersebut dapat dijadikan acuan dalam penyembuhan penyakit dan pengelolaan berbagai tumbuhan obat berbasis kesejahteraan masyarakat dan kelestarian lingkungan bagi masyarakat kabupaten Bima. Metode yang digunakan adalah wawancara secara rinci dan survei lapangan dilanjutkan dengan skrining fitokimia untuk mengetahui kandungan senyawa dalam tumbuhan. Dari hasil penelitian ini diketahui sebanyak 17 jenis tumbuhan obat yang telah dimanfaatkan sebagai obat tradisional. Bagian tumbuhan yang digunakan berupa daun, batang, bunga, akar, rimpang, buah, getah atau lender dengan jenis habitus 33% gulma diikuti oleh herbal (29%), pohon (29%), dan perdu (9%). Sedangkan senyawa yang teridentifikasi dalam tumbuhan obat tersebut yaitu flavonoid, alkaloid, steroid, terpenoid, saponin, dan tannin.